More than walang kwenta A digital ethnography of creation, consumption, and platformization in Ang Walang Kwentang Podcast (AWKP) - Piamonte, Rian Mitchell
In this thesis, I investigate how the creation and consumption of Ang Walang Kwentang Podcast (AWKP), a podcast hosted by filmmakers Antoinette Jadaone and JP Habac, are shaped through the process of platformization. Guided by the concept of Platformization and Participatory Culture, I explore how the hosts and listeners, called ka-emes, experience and negotiate the influence of platforms. Using a digital ethnographic approach, I conducted a month-long participant observation, in-depth interviews with the hosts and 19 ka-emes, and content analysis of 354 episodes of the podcast. Through analysis of these materials, I found that creating the podcast involves the strategic performance of spontaneity while negotiating agency and navigating platform shifts between platforms that surround AWKP: Spotify, YouTube, Facebook, and Discord. On the other hand, ka-emes participate in the life of the podcast through building affective intimacies and support systems, though their participation remains stratified by subscription tiers and platform affordances. Throughout this thesis, I argue that while platforms do influence the creation and consumption of AWKP, the hosts and ka-emes actively negotiate these influences by leveraging their social and cultural capital. Finally, I reflect on the implications of platformization to podcasts, particularly on how creators and consumers balance their agency while engaging with platforms.